MDMA‐assisted psychotherapy for the treatment of PTSD: A systematic review and meta‐analysis of randomized controlled trials (RCTs) - Ghada Shahrour; Kainat Sohail; Safa Elrais; Muhammad Hamza Khan; Javeria Javeid; Khubaib Samdani; Hajra Mansoor; Syed Izhar Hussain; Dhruvikumari Sharma; Muhammad Ehsan; Abdulqadir J. Nashwan (Wiley, 2024)
Abstract Background Post‐traumatic stress disorder (PTSD) is a mental health disorder resulting from exposure to traumatic events, manifesting in various debilitating symptoms. Despite available treatments, many individuals experience inadequate response or significant side effects. Previous reviews suggest promising outcomes with MDMA‐assisted psychotherapy (MDMA‐AT), but limitations prompt the need for a comprehensive evaluation. Methods We searched various online databases and registries such as MEDLINE (via PubMed), Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov to retrieve RCTs that fit our inclusion criteria. We performed meta‐analyses using Review Manager by applying a random‐effects model. Dichotomous and continuous outcomes were pooled as risk ratios (RR) and standard mean difference (SMD), respectively. Results Nine studies with a total of 297 participants with PTSD were included in our meta‐analysis. The control group consisted of inactive doses of MDMA (25-40 mg) or placebo. Our meta‐analysis showed that MDMA‐AT led to a significant reduction in the Clinician‐Administered PTSD Scale for DSM‐5 (CAPS‐5) severity scores as compared to the control group (SMD −1.10, 95% CI: −1.62 to −0.59). More patients in the MDMA‐AT group exhibited significant response (RR 1.59, 95% CI: 1.22, 2.08) and remission (RR 2.32, 95% CI: 1.47 to 3.66) as compared to patients in the control group. There was no significant difference regarding the incidence of ≥1 treatment‐emergent adverse events (TEAE), ≥1 severe TEAE, and suicidal ideation between the two groups. Conclusion MDMA‐AT demonstrates significant efficacy in improving PTSD symptoms, enhancing both response and remission rates in individuals with chronic, treatment‐resistant PTSD, while maintaining a favorable safety profile.